2007
DOI: 10.1108/02683940710721938
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the predictors and consequences of job insecurity's components

Abstract: PurposeThis exploratory study aims to examine the usefulness of distinguishing between the cognitive and emotional components of job insecurity.Design/methodology/approachThis cross‐sectional survey study was undertaken in a sample of 600 civil servants. A series of regressions are employed to test proposed hypotheses.FindingsResults support the treatment of the components of job insecurity as separate variables. The cognitive and emotional components differed in their associations with predictors and conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 46 publications
3
75
0
3
Order By: Relevance
“…This result concurred with Stander and Rothmann (2010) who found that employees were experiencing a higher level of uncertainty about their job continuity (affective job insecurity) than about the continuity of certain dimensions of their job (cognitive job insecurity). [16] Additionally, Huang et al (2012) and Ito and Brotheridge (2007) specified, job insecurity predicts both psychological wellbeing and job performance however cognitive job insecurity has the backhanded impact on performance. [28,29] Supporting the research hypothesis 1, the present study revealed that psychological empowerment and work engagement are positively and significantly correlated with each other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result concurred with Stander and Rothmann (2010) who found that employees were experiencing a higher level of uncertainty about their job continuity (affective job insecurity) than about the continuity of certain dimensions of their job (cognitive job insecurity). [16] Additionally, Huang et al (2012) and Ito and Brotheridge (2007) specified, job insecurity predicts both psychological wellbeing and job performance however cognitive job insecurity has the backhanded impact on performance. [28,29] Supporting the research hypothesis 1, the present study revealed that psychological empowerment and work engagement are positively and significantly correlated with each other.…”
Section: Discussionmentioning
confidence: 99%
“…[16] Additionally, Huang et al (2012) and Ito and Brotheridge (2007) specified, job insecurity predicts both psychological wellbeing and job performance however cognitive job insecurity has the backhanded impact on performance. [28,29] Supporting the research hypothesis 1, the present study revealed that psychological empowerment and work engagement are positively and significantly correlated with each other. Positive correlations were found also between all dimensions of psychological empowerment (meaning, competence, determination, and impact) and all dimensions of work engagement (vigor, dedication, and absorption dimensions).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding affective job insecurity, the results are less equivocal. Generally it appears to relate more to psychological strain (Huang, Lee, Ashford, Chen & Ren, 2010;Ito & Brotheridge, 2007), physical and mental health (Probst, 2003), individuals' impaired self-esteem (Mauno & Kinnunen, 2002), or emotional exhaustion (Pienaar et al, 2013). Van Zyl, Van Eeden, and Rothmann (2013) showed affective job insecurity to predict organisational detachment and avoidance coping, while cognitive job insecurity predicted low organisational identification, less active coping and less seeking of social support.…”
Section: Dimensions Of Job Insecuritymentioning
confidence: 99%
“…This reveals that, although the job features do exist, individuals perceive threats to these job features as a result of the restructuring that is taking place in the organisation. Chovwen and Ivensor (2009) and Ito and Brotheridge (2007), unlike Ugboro and Obeng (2001), found a significant relationship between power/ powerlessness and perceived threats to them. Ugboro and Obeng (2001) found that the relationship between perceived threats to job features and perceived threats to the total job were directly significant.…”
Section: The Dimensions Of Job Insecuritymentioning
confidence: 85%